Early TBI-Induced Cytokine Alterations are Similarly Detected by Two Distinct Methods of Multiplex Assay - Mukherjee, Sanjib; Katki, Khurshed; Arisi, Gabriel M.; Foresti, Maira L.; Shapiro, Lee A. (Frontiers in Molecular Neuroscience, 2011)
Annually, more than a million persons experience traumatic brain injury (TBI) in the US and a substantial proportion of this population develop debilitating neurological disorders, such as, paralysis, cognitive deficits and epilepsy. Despite the long-standing knowledge of the risks associated with TBI, no effective biomarkers or interventions exist. Recent evidence suggests a role for inflammatory modulators in TBI-induced neurological impairments. Current technological advances allow for the simultaneous analysis of the precise spatial and temporal expression patterns of numerous proteins in single samples which ultimately can lead to the development of novel treatments. Thus, the present study examined 23 different cytokines, including chemokines, in the ipsi and contralateral cerebral cortex of rats at 24 hours after a Fluid Percussion Injury (FPI). Furthermore, the estimation of cytokines were performed in a newly developed multiplex assay instrument, MAGPIX (Luminex Corp) and compared with an established instrument, Bio-Plex (Bio-Rad), in order to validate the newly developed instrument. The results show numerous inflammatory changes in the ipsi and contralateral side after FPI that were consistently reported by both technologies.